ARANMULA GLOBAL HERITAGE VILLAGE -A SOCIO-HISTORICAL ANALYSIS - Sreekumar.V.N
The Airport project, in the central part of Kerala went into controversy as the famous Aranmula Sree Parthasarathy temple is in the vicinity of the project. This created strong resistance from the public, and struggle against the project is going on. The green tribunal observed that the project would adversely affect the environment of the area and would have disastrous impact on it. The tribunal rejected the arguments of KGS Group and the Kerala Government. Based on the controversial no objection certificate, submitted by the Kerala Government, the Ministry of Environment and Forests had cleared the project in November, 2013. The court said that KGS Group had not conducted a serious study about the environment impact of the project. On this backgound this study was conducted